TPACK and Learning Strategies in Genetics: A Pedagogical Study - Oky Rizkiana Silaban; Novita Resti; Diki Koerniadi; Kusnadi Kusnadi; Taufik Rahman (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
Genetics is a part of biological science that contains topics such as genetic structure, protein synthesis, cell division, and inheritance of traits. Genetics is one of the most commonly found misconceptions and difficulties in learning this material due to its complex, abstract and rapid development. To overcome these problems, it is necessary to analyse TPACK and analyse various learning strategies used in teaching genetics so that it can be taken into consideration for teachers in teaching genetics in the classroom. This research uses descriptive qualitative method by collecting relevant research in the form of national and international articles available on various websites. From the results of the research, it was found that teachers have applied a variety of models, methods, and media in learning genetics. The success in this learning process certainly depends on the teacher's TPACK analysis skills so that the teacher not only pays attention to the content but also can adjust it to the needs of students.